2019
DOI: 10.3390/ijms20225774
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Dehydrogenase and Tricarboxylic Acid Cycle Enzymes Are Sensitive Targets of Traumatic Brain Injury Induced Metabolic Derangement

Abstract: Using a closed-head impact acceleration model of mild or severe traumatic brain injury (mTBI or sTBI, respectively) in rats, we evaluated the effects of graded head impacts on the gene and protein expressions of pyruvate dehydrogenase (PDH), as well as major enzymes of mitochondrial tricarboxylic acid cycle (TCA). TBI was induced in anaesthetized rats by dropping 450 g from 1 (mTBI) or 2 m height (sTBI). After 6 h, 12 h, 24 h, 48 h, and 120 h gene expressions of enzymes and subunits of PDH. PDH kinases and pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 60 publications
3
32
0
Order By: Relevance
“…Earlier works considered negative outcome of the neurotrauma-decreased enzymatic activities for the energy metabolism during a short-term period up to several days after the trauma ( Sharma et al, 2009 ; Mannino et al, 2018 ; Mkrtchyan et al, 2018b ; Lazzarino et al, 2019 ; Pandya et al, 2019 ). On the other hand, levels of free amino acids and related peptides, such as glutathione, are known to be of marker significance in different neuropathologies, including not only traumatic injuries of CNS, but also individual action of associated pathogenic factors, such as hypoxia and perturbed neurotransmitter metabolism ( Dash et al, 2016 ; Amorini et al, 2017 ; Griffin and Bradshaw, 2017 ; Graf et al, 2020 ; Rana et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier works considered negative outcome of the neurotrauma-decreased enzymatic activities for the energy metabolism during a short-term period up to several days after the trauma ( Sharma et al, 2009 ; Mannino et al, 2018 ; Mkrtchyan et al, 2018b ; Lazzarino et al, 2019 ; Pandya et al, 2019 ). On the other hand, levels of free amino acids and related peptides, such as glutathione, are known to be of marker significance in different neuropathologies, including not only traumatic injuries of CNS, but also individual action of associated pathogenic factors, such as hypoxia and perturbed neurotransmitter metabolism ( Dash et al, 2016 ; Amorini et al, 2017 ; Griffin and Bradshaw, 2017 ; Graf et al, 2020 ; Rana et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The raised NAA concentrations found in the post-injured brain of ILB ® -treated rats may have been due to acetyl-CoA, generated by the enhanced activity of the pyruvate dehydrogenase (PDH) complex, thereby regenerating NAA via the NAT8L-dependent biosynthetic reaction [48,49]. Recently, we found that, following sTBI, the genes controlling the sophisticated enzymatic mechanism regulating the PDH complex activity are expressed in an inhibitory mode causing an overall inhibition of the PDH complex and compromising restoration of energy metabolism of the post-injured brain [50]. Therefore, ILB ® treatment may disinhibit the PDH complex and potentiate acetyl-CoA production at an adequate rate to supply the TCA cycle, as well as to allow NAT8L-mediated condensation of acetyl-CoA with aspartate to form NAA.…”
Section: Discussionmentioning
confidence: 99%
“…PDH represents a cornerstone in cellular energy metabolism, linking glycolysis and Krebs' cycle and lipid metabolism [50]. In this study, PDH activity was failed to detected, whereas the decreased Pdk4 gene expression might suggest the in ux of acetyl-CoA from glycolysis into the Krebs' cycle increased in response to T2 treatment on d 5 post-weaning.…”
Section: Discussionmentioning
confidence: 54%